PENGARUH PERBEDAAN VOLUME PENYIRAMAN PUPUK ORGANIK CAIR (POC) KULIT PISANG KEPOK PADA PEMBIBITAN KAKAO (Theobroma cacao L.) - Rika fitry ramanda; Rosmalinda Rosmalinda; Lia Kafita Sari (Journal of Agro Plantation (JAP), 2022)
The productivity of cocoa (Theobroma cacao L.) in Indonesia has decreased every year. Organic and sustainable fertilization starting from the nursery can be done as an effort to improve the productivity of cocoa. Organic fertilizers consist of 2, namely solid and liquid organic fertilizers. The use of POC can accelerate the absorption of nutrients by plant roots. POC banana peel kepok contains a number of nutrients needed by plants such as C, N, P, K, Fe, Cu, and Zn. This study aims to determine the effect and dose of differences in the volume of watering POC of good kepok banana peels on the growth of cocoa seedlings. This study used a non-factorial Completely Randomized Design (CRD) with 6 treatment levels and 4 replications. Each treatment consisted of 3 plant samples so that 72 samples of seeds were obtained. Parameters observed included plant height (cm), number of leaves (strands), stem diameter (mm), root length (cm), plant dry weight (g). Cocoa seedling growth data were analyzed using Analysis of Variances (ANOVA). If the results of the analysis have a significant effect, it will be continued with Duncan's Multiple Range Test (DMRT) at a level of 5% and data processing using the SAS application version 9.0. Based on the results of the follow-up test (DMRT), the best watering of POC banana peels on the growth of cocoa seedlings (Theobroma cacao L.) was at the volume of watering POC 120 mL.